Determinan Stunting pada Anak Balita di Desa Jambearum Kecamatan Sumberjambe Kabupaten Jember - Dida Tadmar Aiman; Ninna Rohmawati; Sulistyani Sulistyani (Jurnal Kesehatan, 2020)
Stunting is a condition when a toddler fails to grow at his age due to malnutrition from the fetus until the baby is born and usually can be seen at the age of two years. According to Dinas Kesehatan Jawa Timur, Jember is included on 11 districts in Indonesia which are focused on handling stunting. The district with the highest stunting rate in Jember Regency in 2018 is Sumberjambe District. In 2016, the prevalence of stunting in Sumberjambe District was 38.38%, in 2017 was 38.14% and in 2018 was 32.32%. This study aims to look for determinants of the incidence of stunting in toddlers aged 12-59 months in Jambearum Village, Sumberjambe District. This study uses a cross sectional research design. The methode of taking sample uses simple random sampling. Data analysis used the chi square statistical test. The bivariate test showed that there was a significant relationship between food intake, consist of energy (p=0,026), zinc (p=0,045) and calcium (p=0,011) with the incidence of stunting in children under five in Jambearum Village, Sumberjambe Subdistrict, Jember Regency and there was no significant relationship between food intake (protein, iron and phosphorus) , infectious diseases, baby low birth weight status and genetic with the incidence of stunting in toddlers in Jambearum Village, Sumberjambe Subdistrict, Jember Regency.